2019
DOI: 10.1177/0898264319872309
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Physical and Functional Limitations on Health Care Utilization in Older Cancer Survivors: A Medicare Current Beneficiary Survey

Abstract: Objective: This study examines effects of physical and functional limitations on health care utilization among older cancer survivors, compared with those without cancer and without physical and functional limitations. Method: Medicare Current Beneficiary Survey data from 2008 to 2011 were used. Physical limitations (PL), activities of daily living (ADL), and instrumental activities of daily living (IADL) were measured on a 5-point scale. Propensity score weighting was developed using logistic regressions. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Our study makes several novel contributions to the literature. First, although previous studies used a variety of definitions for disability (eg, activities of daily living ( 36 , 37 ), Social Security Disability Insurance ( 13 , 38 )), we provided estimates of the prevalence of functional disability, collectively and by type, based on the standardized HHS definition ( 26 ). Second, prior research largely focused on the association of disability with use of a specific health service (eg, ED) ( 10 , 11 , 13 , 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study makes several novel contributions to the literature. First, although previous studies used a variety of definitions for disability (eg, activities of daily living ( 36 , 37 ), Social Security Disability Insurance ( 13 , 38 )), we provided estimates of the prevalence of functional disability, collectively and by type, based on the standardized HHS definition ( 26 ). Second, prior research largely focused on the association of disability with use of a specific health service (eg, ED) ( 10 , 11 , 13 , 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Measures of functional independence limitation measures were categorized into groups: global cognition (MMSE), frailty (IADL/ADL, FAI, Barthel Index, GFI), and mobility (SPPB, TUG, 6 MW). Thirty-five studies reported global cognition [ 11 , 39 , 41 , 47 , 51 , 55 , 59 , 62 , 63 , 65 , 66 , 69 , 70 , 75 , 76 , 78 , 80 , 85 , 86 , 88 , 89 , 91 , 92 , 94 , 96 , 98 , 101 , 104 , 106 108 , 110 , 115 117 , 121 , 123 ], 55 studies reported frailty characteristics [ 11 , 39 43 , 46 , 47 , 49 52 , 54 , 58 , 61 64 , 68 , 71 83 , 86 , 87 , 90 94 , 98 – 100 , 107 112 , 114 , 115 , 118 123 ], six reported mobility characteristics [ 54 , 55 , 63 , 97 , …”
Section: Resultsmentioning
confidence: 99%
“… 1 Individuals with cancer experience declines in physical function and subsequently may have decreased treatment tolerance, higher health service utilization, and shorter survival. 2 , 3 , 4 Despite interdisciplinary agreement on physical activity guidelines for cancer patients, 5 approximately only 30‐47% of patients meet these guidelines. 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…1 Individuals with cancer experience declines in physical function and subsequently may have decreased treatment tolerance, higher health service utilization, and shorter survival. [2][3][4] Despite interdisciplinary agreement on physical activity guidelines for cancer patients, 5 approximately only 30-47% of patients meet these guidelines. [6][7][8] Existing interventions focused on improving physical functioning in cancer survivors have limitations including generalizability, alignment with patient goals, and cost.…”
Section: Introductionmentioning
confidence: 99%